(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2020)
With 3D Printing in healthcare becoming increasingly common this talk will take a broader look at the potential applications of 3D Printing in hospitals and its associated challenges. Based on the experience at the Basel University 3D PrintLab it will take into account the feedback of referring physicians as well as alternative presentation technologies such as virtual reality.